The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1021/jm00079a002
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic activity of the thiolactone, lactam, lactol, and thiolactol analogs of pilocarpine and a hypothetical model for the binding of agonists to the M1 receptor

Abstract: Pilocarpine isosteres have been synthesized and characterized with regard to their in vitro muscarinic properties. The results indicate that the carbonyl oxygen of the lactone function of pilocarpine is of primary importance for agonist activity with the ether oxygen being of lesser or secondary importance. An X-ray structure determination for the hydrogen O,O'-ditoluoyltartrate salt of thiolactone pilocarpine isostere 2a has been performed. This compound has an unusual pharmacological profile exhibiting M1-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…In recent years, molecular modeling and computational approaches have been used also to aid in the design of muscarinic ligands (Shapiro et al, 1992;Nordvall and Hacksell, 1993;Peng et al, 2006;Johren and Holtje, 2002;Ostopovici et al, 2007). For example, 3D molecular modeling techniques and docking studies using a homology model of bovine rhodopsin have revealed unique interactions between acetylcholine (ACh) and the binding pockets of M 1 -M 5 receptors (Pedretti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular modeling and computational approaches have been used also to aid in the design of muscarinic ligands (Shapiro et al, 1992;Nordvall and Hacksell, 1993;Peng et al, 2006;Johren and Holtje, 2002;Ostopovici et al, 2007). For example, 3D molecular modeling techniques and docking studies using a homology model of bovine rhodopsin have revealed unique interactions between acetylcholine (ACh) and the binding pockets of M 1 -M 5 receptors (Pedretti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, selective M 2 receptor antagonists such as BIBN-99 [Doods et al, 1993, Quirion et al, 1995 and AF-DX 116, [Lapchak et al, 1989;Packard et al, 1990], have been reported to increase synaptic acetylcholine levels and improve the performance of memory tasks in rodents. Several oxotremorine analogs [e.g., BM-5;Engstrom et al, 1987] and pilocarpine isosteres [e.g., thiopilocarpine; Shapiro et al, 1992] exhibit M 1 agonist activity as well as M 2 antagonist properties and are of potential value.…”
Section: Introductionmentioning
confidence: 99%
“…在筛选氯西加酮所做的系统构效研究中没有考虑 到分子中 4-羟乙酰乙酸内酯部分的重要性. 研究表明, 利用电子等排原理将某些化合物内酯部分替换为硫代 内 酯 表 现 出 来 相 似 的 或 者 更 好 的 药 理 活 性 , 例 如 thiopilocarpin [8] , thiobasidalin [9] 和 thioascorbic acid [10] . 因 …”
Section: -(2-氯苄基甲基)-4-甲氧基-2(5h)-呋喃酮] 是一种新型 的抗癫痫药 正在对部分性及继发性全身发作病人进unclassified